Recipient bone marrow‐derived stromal cells prolong graft survival in a rat hind limb allotransplantation model. Issue 6 (17th November 2016) - Ikeguchi, Ryosuke; Kakinoki, Ryosuke; Ohta, Souichi; Oda, Hiroki; Yurie, Hirofumi; Kaizawa, Yukitoshi; Mitsui, Hiroto; Aoyama, Tomoki; Toguchida, Junya; Matsuda, Shuichi
Abstract : Background: Recent studies have indicated that bone marrow‐derived stromal cells (BMSCs) have immunomodulatory properties that suppress the T cell responses that cause graft rejection. The purpose of this study is to evaluate the effect of recipient BMSCs intravenous infusion for immunomodulation in a rat vascularized composite allotransplantation model. Methods: A total of nine Wistar (WIS) rats and thirty Lewis (LEW) rats were used. BMSCs were harvested from three LEW rats. Twenty‐four LEW rats were used as recipients and divided randomly into four groups: BMSC group, FK group, UT group, and Iso group. In the BMSC group, orthotopic rat hind limb transplantation was performed between WIS donor and LEW recipient rats. Recipient rats were injected intravenously with 2 × 10 6 recipient BMSCs on day 6, and with 0.2 mg/kg/day tacrolimus administered over 7 days ( n  = 6). In the FK group, recipient rats were treated with tacrolimus alone ( n  = 6). Rats in the UT group received no immunosuppressive treatment ( n  = 6). In the Iso group, transplantation was performed from three LEW donor rats to six LEW recipient rats without any immunosuppressive treatment ( n  = 6). Graft survival was assessed by daily inspection and histology. The immunological reactions of recipients were also evaluated. Results: The graft survival of recipient rats in the BMSC group (24.5 days) was significantly prolonged in comparison with that of the FK group (18 days) ( P  < .01). Cytokine expression analysis of the skin of grafted limbs showed that BMSCs treatment significantly decreased IFN‐γ mRNA expression of the BMSC group (0.138 ± 0.045) in comparison with that of the FK group (1.049 ± 0.167) ( P  = .0001). Recipient rats in the BMSC group had significantly reduced serum IFN‐γ cytokine levels (1.571 ± 0.779 pg/ml) in comparison with that of the FK group (7.059 ± 1.522 pg/ml) ( P  = .001). In in vitro study, BMSCs induce T cell hyporesponsiveness in a mixed lymphocyte reaction. Conclusion: BMSCs induce T cell hyporesponsiveness and prolong graft survival in the rat vascularized composite allotransplantation model. BMSCs exhibit immunomodulatory properties against acute rejection that can be realized without the need for significant recipient immunosuppression.